Aspects Of Spirituality And Religiusity In Patients End Stage Renal Disease (ESRD) - Muhammad Putra Ramadhan; Krisna Yetti (Jurnal Keperawatan Respati Yogyakarta, 2020)
Comprehensive and holistic nursing care by professional nurses is continuously improved, especially nursing care in ESRD patients. This has an impact on the importance of knowing the potential to be revamped so that the poor quality of life in ESRD patients can be enhanced one of the aspects of spirituality and religiusity included in the comprehensive and holistic. The aim of this study was to study the aspects of spirituality and religiusity in End Stage Renal Disease (ESRD) patients. This study uses a Litelature review was chosen as the method used for this study by collecting litelature from ProQuest, Wiley Online, and Scientdirect databases using the keywords "sentimental and ESRD Spritual", "Religious beliefs and ESRD "," Spiritual Beliefs and ESRD ", and "Religious and Spiritual Beliefs and ESRD" and the chosen circuit are full text journals published from 2010 to 2019, and written in English. The results is selected journal has been chosen to show that the spiritual and religious aspects are associated with QoL, HRQoL and Self-Caring in the ESRD patients undergoing HD. The relationship formed is a positive relationship where the better aspect of spirituality and religiality of ESRD patients undergoing HD then QoL, HRQoL, and Self-Caring patients are also good. In addition, the themes formed from the results of qualitative analysis, namely decision-making, the ESRD patients, participants ' spiritual pressures, self-caring meaning, self-caring action, Islamic influence on self-caring, and cultural influences on Self-caring. The aspect of spirituality and religiusity is the provision of comprehensive and holistic care services. Both aspects are proven to have a good impact on the Quality of Life (QoL), Health-Related Quality of Life (HRQoL), and self-caring in the ESRD patients undergoing HD.